Tratados internacionais de direitos humanos: análise à luz do princípio da prevalência dos direitos humanos nas relações internacionais do Brasil - Portela, Paulo Henrique Gonçalves (2007)
The principle of the prevalence of human rights, which is one of the governing principles of the international relations of Brazil, obliges Brazilian State to set as a priority of national foreign policy the promotion of a deeper involvement of Brazil with the protective scheme shaped by international treaties on human rights, which defines as paramount obligation of Law to protect human dignity. The aforementioned human rights treaties impose not only the involvement of Brazil in initiatives aimed at improving the situation of those rights all over the world, but also the legal obligation of taking all the measures deemed as necessary for the human rights to become a reality in national level. Taking this into account, the legal frame related to the situation of human rights treaties when incorporated into internal Brazilian Law becomes highlighted. The 1988 Constitution of the Federative Republic of Brazil includes rules regarding the hierarchy of those treaties in Brazilian juridical order, especially paragraphs 2 and 3 of article 5, which open the path for the rights consecrated by human rights conventions to reach constitutional status. However, the issue is still controversial, and juridical practice demonstrates that notions concerning the non-constitutional character of human rights treaties continue to endure, clearly violating the constitutional value of the prevalence of those rights. The assurance of the primacy of human rights demands, primarily, placing those rights in the highest level of Brazilian juridical system, namely the constitutional level. In any case, the prevalence of human rights in Brazilian international relations is not to be assured unless the constitutional system embraces the principle of the prevalence of rule that is most favorable, standard conceived by the International Law of Human Rights in order to solve conflicts involving rules protecting human dignity.